7(n+9)-6(7n-3)=

Simple and best practice solution for 7(n+9)-6(7n-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(n+9)-6(7n-3)= equation:


Simplifying
7(n + 9) + -6(7n + -3) = 0

Reorder the terms:
7(9 + n) + -6(7n + -3) = 0
(9 * 7 + n * 7) + -6(7n + -3) = 0
(63 + 7n) + -6(7n + -3) = 0

Reorder the terms:
63 + 7n + -6(-3 + 7n) = 0
63 + 7n + (-3 * -6 + 7n * -6) = 0
63 + 7n + (18 + -42n) = 0

Reorder the terms:
63 + 18 + 7n + -42n = 0

Combine like terms: 63 + 18 = 81
81 + 7n + -42n = 0

Combine like terms: 7n + -42n = -35n
81 + -35n = 0

Solving
81 + -35n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-81' to each side of the equation.
81 + -81 + -35n = 0 + -81

Combine like terms: 81 + -81 = 0
0 + -35n = 0 + -81
-35n = 0 + -81

Combine like terms: 0 + -81 = -81
-35n = -81

Divide each side by '-35'.
n = 2.314285714

Simplifying
n = 2.314285714

See similar equations:

| y=.4*-27 | | 4X-24=36 | | y=.4x*27 | | 1/x=2/x+2 | | 3x-12=1x | | 7x+5=37 | | 1/25-5=x | | 322yds=73yds | | X(x-3)=36 | | -0.7x=1.4 | | 4y-8=64 | | 2.35+p=49.25 | | (X/5)=(6/35x)+2 | | v/3+17=30 | | 12=u/2-13 | | 11(q-4)-2(7q+4)= | | u/5=6.25 | | 5/6x-1/6y=19/6 | | h(t)=-16t^2+26t+6 | | p=20n-(12n+200+2.5n) | | y=10x+30000 | | 6(n-6)=12 | | 6y=15.36 | | 7007cm^2=77cm | | 9.6=w/3 | | 8=v/20.48 | | 15m+75-24m+21= | | 2+.70x+4.00=27.00 | | z^2+18=10 | | 2=E+2 | | 2-(x+3x-(x+6)-3)=3 | | 3-2/3x=x/2+1 |

Equations solver categories